Mental health status of Italian elderly subjects during and after quarantine for the COVID‐19 pandemic: a cross‐sectional and longitudinal study. Issue 4 (6th May 2021) - Maggi, Gianpaolo; Baldassarre, Ivana; Barbaro, Andrea; Cavallo, Nicola Davide; Cropano, Maria; Nappo, Raffaele; Santangelo, Gabriella
Abstract: Background: The elderly are more vulnerable to COVID‐19 and therefore need to adopt long‐term social distancing measures. The duration of quarantine impacts the psychological status of the general population. However, until now no study has explored the psychological impact of the pandemic and quarantine together with longitudinal changes in the mental health status of Italian elderly. Methods: An online questionnaire including an assessment of depression, anxiety, anger, post‐traumatic stress, subjective cognitive failures, resilience, coping style, and other dimensions related to the pandemic was completed by participants during (T0) and two months after the end (T1) of the quarantine. Results: The sample recruited at T0 included 334 elderly participants. About 45% of the participants experienced depression, anxiety, or anger. Moreover, more fear of getting infected was related to more severe depression, anxiety, and anger, but resilience was found to mediate these relationships. More severe depressive and anger symptoms were related to more severe cognitive failures. No significant difference was observed in mental health scores between T0 and T1. Finally, more severe depression at T0 was associated with the development of post‐traumatic stress symptoms at T1. Conclusions: The fear of getting infected, probably due to perceived vulnerability to disease, seems to play a crucial role in the development of psychological symptoms in the elderly, but resilience seems to mediate the impact of fear. The presence of long‐term psychological consequences and the possible risk of developing PTS symptoms in the elderly suggest the need for targeted interventions to reduce possible long‐term psychological and cognitive consequences.